Revised Seventh Five Year Plan 1985-90 Vol I Introduction - Planning Commission (Planning Commission, 1985)
The magnitude of change which Lakshadweep has seen in the course of planned development, viz. the changes in lifestyle, occupational pattern, in the facilities and comforts available to the people, in the level of education, and also in income levels, is probably greater, and is certainly more striking, than in almost any other part of the country. One reason for this is, of course, the very low base from which the developmental effort began.
Planning Department
Planning Department